PENGUATAN PENDIDIKAN KARAKTER BERBASIS KEPEMIMPINAN KHARISMATIK SULTAN AGENG TIRTAYASA BAGI PESERTA DIDIK DI WILAYAH BANTEN - Rochani; Achmad Hufad; Aan Hendrayana; Suroso Mukti Leksono (Universitas Sultan Ageng Tirtayasa, 2021)
The condition of Indonesian society, especially in Banten, is currently starting to occur many changes. One of them is the loss of character values. The saddest is that people forget about local heroes and their character traits represented the characteristics of Indonesian society. This research aims to explore the character of a local hero, namely Sultan Ageng Tirtayasa, to be reinvested in the world of education. The research used literature study method. The results showed that Sultan Ageng Tirtayasa had many positive characters that stood out including being honest, trustworthy, dignified, fair, and religious. These characters are very relevant and important to be reinvested in education. This condition is in line with the government's program to run the Character Strengthening Program in the world of education.